2021
DOI: 10.1107/s2052520621003309
|View full text |Cite
|
Sign up to set email alerts
|

A survey of thermal expansion coefficients for organic molecular crystals in the Cambridge Structural Database

Abstract: Typical ranges of thermal expansion coefficients are established for organic molecular crystals in the Cambridge Structural Database. The CSD Python API is used to extract 6201 crystal structures determined close to room temperature and at least one lower temperature down to 90 K. The data set is dominated by structure families with only two temperature points and is subject to various sources of error, including incorrect temperature reporting and missing flags for variable-pressure studies. For structure fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…22 The anisotropic nature of thermal expansion in molecular crystals has been discussed in recent studies and, indeed, is more commonly the norm than the exception. 27,28…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The anisotropic nature of thermal expansion in molecular crystals has been discussed in recent studies and, indeed, is more commonly the norm than the exception. 27,28…”
Section: Introductionmentioning
confidence: 99%
“…22 The anisotropic nature of thermal expansion in molecular crystals has been discussed in recent studies and, indeed, is more commonly the norm than the exception. 27,28 We recently developed a new approach to improve PXRDbased comparison methods using anisotropic volume corrections. 23 The method was applied to identify candidate structures generated from first-principles crystal structure prediction (CSP) that match known experimental structures and, in the process, identified two uncredited matches from the 6th CSP blind test.…”
Section: Introductionmentioning
confidence: 99%
“…14 A recent CSD survey by Bond shows that uniaxial NTE is more common than biaxial NTE in organic materials. 15 In addition, few single-component organic crystalline compounds have been reported for unusual thermal expansion properties. 3 g , r ,16…”
Section: Introductionmentioning
confidence: 99%
“…NTE materials find possible application in various fields such as cookwares, electronics, optical devices, thermo-mechanical instruments, and aerospace engineering. ,, A certain class of compounds are known to exhibit the NTE property, such as metal oxides, , cyano-bridged metal complexes, and Prussian blue analogues, and very few organic materials are known for either uniaxial or biaxial , NTE. Since thermal expansion of the materials with non-cubic lattice are anisotropic in nature due to anisotropic supramolecular interactions along different directions, linear NTE (axial NTE) has been reported for several inorganic and organic compounds. , NTE with large CTE is rare in inorganic materials. , In 2008, Goodwin and co-workers have described colossal PTE and NTE in a cyano-bridged Ag–Co complex (Ag­[Co­(CN) 6 ]) . Kepert et al have shown the same phenomenon in a nanoporous coordination framework material induced due to spin crossover …”
Section: Introductionmentioning
confidence: 99%
“…NTE materials find possible application in various fields such as cookwares, electronics, optical devices, thermomechanical instruments, and aerospace engineering. 1,2,8−10 A certain class of compounds are known to exhibit the NTE property, such as metal oxides, 11,12 cyano-bridged metal complexes, 13−16 and Prussian blue analogues, 17−19 and very few organic materials are known for either uniaxial or biaxial 20,21 NTE. Since thermal expansion of the materials with non-cubic lattice are anisotropic in nature due to anisotropic supramolecular interactions along different directions, linear NTE (axial NTE) has been reported for several inorganic and organic compounds.…”
Section: ■ Introductionmentioning
confidence: 99%